Mengembangkan Kemampuan Berpikir Kritis Matematis Siswa Kelas V Sekolah Dasar Menggunakan Pendekatan Realistic Mathematic Education (RME) dan Visualisasi Spasial - Yunianingsih, Elih; Meiliasari, Meiliasari; Jaya, Indra (Cetta: Jurnal Ilmu Pendidikan, 2024)
The basis for this research was the low mathematical critical thinking skills among fifth-grade students of SDN Kubang 02. The objective was to develop their mathematical critical thinking skills using the Realistic Mathematics Education (RME) approach and spatial visualization. This research is a classroom action research (PTK) with Kemmis and McTaggart model consisting of three cycles. Data collection was taken from observation and test data, while data analysis used qualitative and quantitative comparative descriptive methods by comparing data results from each cycle. The researcher's findings are that using the RME approach and spatial visualization in the mathematics learning process can develop students' mathematical critical thinking skills. This can be seen from acquiring mathematical critical thinking ability test results that have increased each cycle. In the pre-cycle students who obtained a test score ≥ 65 only reached 9 students or 18%, in cycle I experienced a development of 24 students or 49%, in cycle II experienced a development to 31 students or 63%, in cycle III continued to experience development until it reached 40 students or reached a percentage of 82%. Development can also be seen from the average value of students' mathematical critical thinking skills which increased from 50 in pre-cycle conditions, to 61 in cycle I, in cycle II it increased to 69, and in cycle III it increased again to 73. Based on the data obtained, it can be concluded that the use of the RME approach and spatial visualization is effective in developing the mathematical critical thinking skills of grade V students at SDN Kubang 02.